Kewenangan Hakim dalam Menyatakan Gugatan idak Dapat di Terima Niet Ontvankelije Verklaard dalam Perkara Perdata (Putusan Nomor 82/Pdt.G/2025/Pn Kwg) - Edward Japanis Ratu Dewan; Sartika Dewi; Muhamad Abas (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
This research discusses the authority of judges in declaring a lawsuit inadmissible (Niet Ontvankelijke Verklaard/NO) in civil cases based on Decision Number 82/Pdt.G/2025/PN Kwg. The issues examined in this study relate to the application of formal requirements of a lawsuit and the authority of judges in rendering an NO decision due to errors in determining legal subjects (error in persona). This study aims to analyze the application of civil procedural law regarding the formal requirements of a lawsuit and to examine the authority of judges in declaring a lawsuit inadmissible. The research method used is normative juridical with statutory and case approaches. The legal materials used consist of primary, secondary, and tertiary legal materials obtained through library research and analyzed qualitatively. The results of the study indicate that the formal requirements of a lawsuit hold a very important position in civil procedural law. Errors in determining legal subjects, particularly involving a party who has passed away without involving the heirs, result in a formally defective lawsuit and cause it to be declared inadmissible (Niet Ontvankelijke Verklaard). In Decision Number 82/Pdt.G/2025/PN Kwg, the judges exercised their authority in accordance with civil procedural law to maintain legal certainty and orderly judicial proceedings. However, the application of such authority is considered to be overly formalistic because it did not provide an opportunity to amend the lawsuit, thereby giving less attention to substantive justice for the plaintiff.